1999
DOI: 10.1007/s003359901114
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer and the human gene for ribonucleotide reductase subunit M1 (RRM1)

Abstract: LOH11A is a region of Chromosome (Chr) 11p15.5 where 75% of lung cancers show loss of heterozygosity (LOH). Clinical and cell biological studies suggest that LOH11A contains a tumor/metastasis suppressor gene. We have mapped this region (650 kb) using overlapping genomic P1/PAC/BAC clones, and one of the genes that we have identified is RRM1. This gene encodes the large subunit (M1) of ribonucleotide reductase, the heterodimeric enzyme that catalyzes the rate-limiting step in deoxyribonucleotide synthesis. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 20 publications
2
24
0
1
Order By: Relevance
“…This provides a sound basis for the identi®cation and functional analysis of genes in the region that may play a role in the pathogenesis of lung cancer. Functional analyses by microcell-mediated chromosome transfer and clinical studies have suggested that loss of this critical region results in a more aggressive tumor phenotype (Bepler et al, 1998O'Briant et al, 1997), and analysis of two known genes, SSA/Ro52 and RRM1, has not provided evidence for mutational inactivation Pitterle et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides a sound basis for the identi®cation and functional analysis of genes in the region that may play a role in the pathogenesis of lung cancer. Functional analyses by microcell-mediated chromosome transfer and clinical studies have suggested that loss of this critical region results in a more aggressive tumor phenotype (Bepler et al, 1998O'Briant et al, 1997), and analysis of two known genes, SSA/Ro52 and RRM1, has not provided evidence for mutational inactivation Pitterle et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Two genes, SSA/Ro52 and RRM1, within this minimal region of LOH have been studied for potential inactivating mutations, and none were identi®ed Pitterle et al, 1999). Few other expressed sequence tags (ESTs) and putative genes have been localized to this region .…”
Section: Introductionmentioning
confidence: 99%
“…RRM1, localised in 11p15.5, also acts as a putative tumour suppressor gene (Pitterle et al, 1999). 11p15.5, also known as LOH11A, is frequently lost in NSCLC, and loss of heterozygosity in this region has been correlated with poor survival in resected NSCLC patients (Bepler et al, 2002).…”
mentioning
confidence: 99%
“…Clinical and cell biological studies suggest that LOH is an important tumor‐suppressor gene region in lung cancer 15, 16. Moreover, RRM1 is a metastasis suppressor gene through PTEN‐regulated pathways in lung cancer 17.…”
Section: Discussionmentioning
confidence: 99%